EOKA: From Thought to Action - İsmail Şahin (Yakın Dönem Türkiye Araştırmaları)
The purpose of this study is to examine the establishment process of EOKA within the framework of other important events concerning the history of Cyprus. The fact that comprehensive and adequate academic studies have not been conducted on this organization until today, constitutes the reason for this study. The research focused on the historical period from the birth of EOKA’s founding idea to its first action. Throughout the research, important turning points in the history of Cyprus were also men-tioned. Thus, it was thought that the subject of the article would be easier to understand. The article argues that EOKA is a paramilitary organization that was established to put into practice the enosis through weapons. It was revealed in the research that EOKA is an organization that emerged as a result of the failure of the enosis diplomacy of Greek Cypriot representatives and Greek governments. In the study, memoirs, archive documents, articles and books about the subject and newspapers of the period were used.